Clonal Relationship and Resistance Profiles Among ESBL-Producing Escherichia coli - Dolatyar Dehkharghani, Alireza; Haghighat, Setareh; Rahnamaye Farzami, Marjan; Rahbar, Mohammad; Douraghi, Masoumeh (Frontiers in Cellular and Infection Microbiology, 2021)
AmpC β-lactamases hydrolyze all β-lactams except cefepime and carbapenems. The study of AmpC-producing E. coli has high priority for the infection control committee. This research is aimed to investigate the resistant urinary AmpC-generating E. coli isolates and identify their genetic variety. Some 230 E. coli isolates from patients suffering urinary tract infection symptoms were studied in 2017–2018 to assess their susceptibility toward antimicrobial agents. AmpC gene was evaluated by PCR and molecular typing using the 10-loci MLVA method. MLVA images were examined by BioNumerics 6.6 software through the use of the UPGMA algorithms. Thirty-eight AmpC-generating E. coli isolates were detected. The most abundant determinant was blaCIT and blaEBC, blaFOX, and blaDHA had the next ranks, respectively. Six major clusters and a singleton were identified by MLVA. AmpC beta-lactamases in urinary isolates of E. coli in the hospital under study and high rate of additional resistance to gentamicin, cotrimoxazole and ciprofloxacin. The most frequent gene determinant of AmpC beta-lactamase was blaCIT and vary depending on time and geographical location.